The Effectiveness of Consumption between Temulawak Extract (Curcuma xanthorrhiza) and Katuk Leaves (Sauropus androgynous) towards Breast Milk Launch in Postpartum Mothers - Mayasari Putri Ardela; Siti Aminah; Supraptiningsih; Faradilla Kartika Nuvitaningrum; Anis Yuliana (Journal of Global Research in Public Health, 2021)
Breast milk is the natural first food for babies. Its provides all the energy and nutrients for babies in the first months of life. Breastfeeding is an excellent way of providing ideal food for the healthy growth and development of babies. Efforts to increase breast milk production are by consuming foods or ingredients that are believed to increase milk production. Temulawak (Curcuma xanthorrhiza) contains essential oils that can Temulawak contains essential oils that can stimulate breast milk production. In addition, katuk leaves (Saoropus androgynus) also have the same effect on milk production. The purpose of this study was to determine the difference in the effectiveness of consumption of temulawak extract and katuk leaves on the breast milk's flow in postpartum mothers. This research is a pre-experimental type with a two group pretest-posttest approach to 16 postpartum mothers who experience problems with the smooth flow of breast milk in each group. The results of the study were analyzed using the Mann Whitney test with p-value > (0.05), which means that there is no difference in the effectiveness of consuming temulawak extract and katuk leaves on the smooth flow of breast milk in postpartum mothers.